THE PREVALENCE OF SOCIAL ANXIETY DISORDER (SAD) AMONG HIGHER EDUCATION STUDENTS IN MALAYSIA - Shalini Dialan; Nuzsep Almigo (Universitas Pendidikan Indonesia, 2021)
The research is focusing on the Prevalence of Social Anxiety Disorder (SAD) Among Higher Education Students in Malaysia. Social Anxiety Disorder is characterized by an excessive fear of being negatively evaluated by others in social situations. The present study adopted a qualitative approach to explore the experiences of University students affected from the symptoms of Social Anxiety Disorder. The sample is consisted of three female university students. One of the female university student experienced Social Anxiety Disorder and was diagnosed. The data was obtained by semi-structured interviews and analyzed by using Interpretative Phenomenological Analysis (IPA). The results obtained demonstrate that Social Anxiety is a complex disorder affecting an individual emotions, cognitions and physiological. There are several factors that contributing to Social Anxiety Disorder such as bullying in school, rejection from peer and past experiences. Coping mechanism and strategies also emerged as themes